Judgment night - Levy, Gene; Hopkins, Stephen; Largo Entertainment; JVC Entertainment (United States : Largo Entertainment, 1993)
Four pals are on their way to a boxing match, but gets stuck in heavy traffic. To get to the boxing match in time they take the first exit they find to find another way to the venue. As they are driving around lost in gang-land they get stuck and witness a brutal murder. The killer wants no witnesses and tries to kill them too. The four pals get away the first time, but the killer is soon back on their tail again while they are trying to find help in the middle of nowhere
Title fro title screen
Screenplay by Lewis Colick ; executive producer, llyoyd H. Segan and Marilyn Vance ; editor, Timothy wellburn
Cast: Emilio Estevez, Cuba Gooding Jr., Denis Leary, Stephen Dorff, Jeremy Piven, Peter Greene, Erik Schrody, Michael Wiseman, Michael DeLorenzo, Relioues Webb, Will Zahrn, Eugene Williams, Christine Harnos, Galyn Görg, Angela Alvarado
DVD Format
Dolby Digital
In English with optional English, Malay or Mandarin subtitles
Keywords: Gangster films; Murder -- Drama; Suspense in motion picture